2014
DOI: 10.7224/1537-2073.2013-013
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Mood Measures for People with Multiple Sclerosis

Abstract: Background: Valid assessments are needed in order to identify anxiety and depression in people with multiple sclerosis (MS). The objective of this study was to assess the validity of questionnaire measures of mood in people with MS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
89
2
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(102 citation statements)
references
References 21 publications
4
89
2
7
Order By: Relevance
“…This notion is supported by a recent study which has found that the HADS and Beck Inventories may not be valid measures of psychiatric illness in OP-exposed participants (Harrison & Mackenzie Ross, under review); nor in many other patient groups with concurrent ill-health symptoms (e.g. Golden et al, 2007;Mitchell et al, 2010;Poole et al, 2006;Watson et al, 2014). Thus it is unclear how meaningful the information derived from self-report measures is in clinical, or real-world terms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This notion is supported by a recent study which has found that the HADS and Beck Inventories may not be valid measures of psychiatric illness in OP-exposed participants (Harrison & Mackenzie Ross, under review); nor in many other patient groups with concurrent ill-health symptoms (e.g. Golden et al, 2007;Mitchell et al, 2010;Poole et al, 2006;Watson et al, 2014). Thus it is unclear how meaningful the information derived from self-report measures is in clinical, or real-world terms.…”
Section: Discussionmentioning
confidence: 99%
“…Although self-report measures may be useful for screening purposes in large populations, it is not always clear whether findings are comparable with what would be derived from structured clinical interviews undertaken by mental health professionals using internationally agreed diagnostic criteria for mental disorders. Indeed, previous research with other patient cohorts (including multiple sclerosis, cancer, cardiomyopathy, hepatitis C) has shown that self-report measures may not be good indictors of psychiatric disorder (Golden et al, 2007;Mitchell et al, 2010;Poole et al, 2006;Watson et al, 2014), and a recent study suggests this may be particularly true for research with OP exposed groups (Harrison & Mackenzie Ross, under review). Structured interviews standardise the coverage of specific psychiatric issues (thus reducing the possibility of missed diagnoses) and require the systematic appraisal of relevant symptoms, to reduce misdiagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the heterogeneity of included studies (n = 4) with respect to the HADS-A had a sensitivity of 90% and a specificity of 92% compared with the SCAN. 21 This cut-point produced a positive predictive value of 82%, a negative predictive value of 96%, and an AUC of 0.94 for any anxiety disorder. 21 Compared with the BAI (cut-point ≄16), the HADS-A with a cut-point of 7 had a sensitivity of 71% and a specificity of 63%, which was the optimal cut-point according to ROC analyses.…”
Section: Resultsmentioning
confidence: 99%
“…21 This cut-point produced a positive predictive value of 82%, a negative predictive value of 96%, and an AUC of 0.94 for any anxiety disorder. 21 Compared with the BAI (cut-point ≄16), the HADS-A with a cut-point of 7 had a sensitivity of 71% and a specificity of 63%, which was the optimal cut-point according to ROC analyses. 22 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation